The Influence of Product Quality and Brand Image on Loyalty Through Consumer Satisfaction on Honda Automatic Motorcycles in Palembang City - Nizar, M. Ahlun; Rahayu, Sri; Trihandayani, Zaleha (International Journal of Management Science and Information Technology, 2025)
Research showed determine the effect while product high quality and brand image by good customer loyalty through satisfy with Honda brand automatic motorcycles Palembang City. Condition this research have associative type. The variables used are product quality, good brand image, consumer satisfaction and consumer loyalty. A sample of 100 people was select to accidental sample.  Data in reseach used is primary data and make a questionare data wich collectif method. Data when analysis technique is method modeling structural equation (SEM) with the Lisrel Program Application. The results in this research of indicate this study are: Product have quality and showed image brand have a value of positif and effect significant to customer satisfaction. Product quality and brand image have a positif and effect of significant on costumer loyalty. Satisfaction has customer no effect significant to customers make the loyalties. Meanwhile, consumer satisfaction strengthens the influence by high product make the quality have brand image costumer loyalty.